El "Decamerón" tras el "Curial e Güelfa" (Estudios Humanísticos. Filología, 1997)
After some brief theoretical notes on the introduction by the prehumists, on the new techniques of the sources, the presence ofDecameron is followed by the text of the Catalan novel Curial e Güelfa. In book II you can see this in two passages relating to the idea of honour, whilst two Decameronic tales about King Peter the Great practically form book III. The autor, in the same style as Petrarch (and Bernat Metge) by means of the Boccaccio texts gives a turn to Bocccaccio's love moral. The last tale (viiX), based on recognition, seems to reveal that it is a novel written in code, with the intention of moving certain readers towards the behaviour which the main characters illustrate. This serves as heroic example in the lovetheme, agreeing with the ethic which marks an initial Petrarchist reference and which is supported by the classics.